Diabetes subgroups and risk for complications: The Multi-Ethnic Study of Atherosclerosis (MESA) - Bancks, Michael P. (J Diabetes Complications, 2021)
AIMS: To characterize diabetes subgroups among a multi-ethnic cohort and assess risk for incident complications. METHODS: We included 1587 participants from the Multi-Ethnic Study of Atherosclerosis with diabetes. We characterized eight diabetes subgroups according to absolute thresholds for disease characteristics: age at diabetes diagnosis (≤45 years), fasting glucose (FG ≥7.7 mmol/l; ≥140 mg/dL), and waist circumference (women ≥105 cm; men ≥110 cm). We estimated risk for mortality, incident cardiovascular disease, chronic kidney disease, heart failure, dementia, and retinopathy, respectively, over 17 years after adjustment for demographics, behavioral, clinical risk factors, and cohort attrition. RESULTS: The subgroup with both high FG and early age at onset was associated with higher risk for death, CVD, heart failure, CKD, and retinopathy and the subgroup with both early age at onset and high waist circumference was associated CVD, heart failure, CKD, and retinopathy. The subgroup that met all three high-risk thresholds had greater risk for death, heart failure, CKD, and retinopathy. We did not observe evidence for synergistic or antagonistic joint effects of the high-risk characteristics for any outcome. CONCLUSIONS: Our work supports differential risk for various diabetes complications among exclusive subgroups defined by age at diabetes onset, fasting glucose, and central adiposity.